Celery herb essential oil in the formulation of anti-dandruff hair tonic against Pityrosporum ovale - Riska Surya Ningrum; Antonius Budi Prasetyo; Alfinda Novi Kristanti (Jurnal Kimia Riset, 2017)
Abstract Essential oil from Apium graveolens (celery), a species belonged to Apiceae, was isolated, identified, and tested its activity against fungi Pityrosporum ovale, fungi that cause dandruff problem. Essential oil isolation was conducted by steam distillation. The identification with GC-MS showed that the major compound of celery essential oil was 3-isobutylidenphalide. The anti-fungal activity test was performed using pure celery oil and celery oil added with virgin coconut oil (VCO) and paraffin oil that are usually used as components in hair tonic formulation. The bioactivity test showed that celery oil, whether in pure form or in hair tonic formulation exhibited excellent growth inhibition activity of Pityrosporum ovale Keywords : essential oil, celery, Apium graveolens, hair tonic, anti-dandruff, Pityrosporum ovale